Students' interest in participating in volleyball extracurricular - Mugi, Mugi; Wiraguna, Adi; Suganda, Mikkey Anggara (Universitas Tanjungpura, 2022)
This study aims to determine the level of student interest in participating in volleyball extracurricular activities at MTs Manbaul Hikam, as well as analyze the influence of external factors on this interest. The background of this study is based on the low participation of students in sports extracurricular activities, especially volleyball, which is suspected to be influenced by the environment, teacher support, availability of facilities, and the role of parents. This study uses a quantitative approach with a survey method. The instrument used is a closed questionnaire which is compiled based on external factor indicators. The research sample consisted of students in grades VII and VIII who were active or inactive in extracurricular activities. The data was analyzed descriptively quantitatively using percentages and graph visualization. The results showed that most students (53.80%) were in the category of low interest in volleyball extracurriculars, followed by students with high interest (35.90%), very high (7.70%), and very low (2.60%). These findings suggest that external factors have a significant influence on student interest. Lack of environmental support, limited facilities, and lack of involvement of teachers and parents are the main causes of low student interest. In conclusion, increasing students' interest in volleyball extracurricular activities requires intervention from the school through strengthening the role of coaches, improving infrastructure, and collaboration with parents. This research is expected to be the basis for the development of more effective extracurricular coaching strategies.